Comprehensive Structure of the Female Marine Water-Strider Asclepios annandalei Distant, 1915 from Pranburi River Estuary, Thailand: New Information for the Genus Asclepios - Pisit Poolprasert,; Sinlapachai Senarat,; Jes Kettratad,; Gen Kaneko,; Ezra Mongkolchaichana,; Natthawut Charoenphon,; Narit Thaochan, (Tropical Life Sciences Research, 2022)
The objective of this study was to describe the structure and histochemistry of the systemic organs in the female marine water-strider Asclepios annandalei from Pranburi river estuary, Thailand. Results from this study revealed for the first time that the integumentary system of this species consisted of three layers including epicuticle, exocuticle and endocuticle. The muscular system apparently contained only skeletal muscle along the body. In the urinary system, we observed well-developed Malpighian tubules, each of which was covered with the simple cuboidal epitheliums. These epitheliums also contained the secretory granules that were reacted positively with periodic acid Schiff (PAS). The digestive system of this species was composed of three distinct parts including foregut, midgut and hindgut. The respiratory system was composed of the respiratory organ, which was rarely found near the integument system. This organ was lined with a simple squamous epithelium. Two regions of nervous system, i.e., frontal ganglion connected to the eye structure and ventral nerve cord, were found. Each ganglion basically consisted of two layers, outer cortex and inner medullae. The outer cortex contained three types of cells, including neurosecretory cells, neuroglial cells and neurons. The cytoplasmic inclusion of neurosecretory cells contained secretory granules, which reacted positively with PAS, indicating the presence the glycoprotein. The neuroglia and neuron were also observed in the inner medullae layer. The female reproductive system (the ovarian structure, the reproductive tract and the accessory organ) of this gerrid species was seen under histological sections. The well-developed integument system and Malpighian tubule as well as the abundant respiratory organ is a characteristic of this species, which might be useful for the adaption to the estuarine condition.